Pulsed Infrared Stimulation of Vertical Semicircular Canals Evokes Cardiovascular Changes in the Rat - Rice, Darrian; Martinelli, Giorgio P.; Jiang, Weitao; Holstein, Gay R.; Rajguru, Suhrud M. (Frontiers in Neurology, 2021)
A variety of stimuli activating vestibular end organs, including sinusoidal galvanic vestibular stimulation, whole body rotation and tilt, and head flexion have been shown to evoke significant changes in blood pressure (BP) and heart rate (HR). While a role for the vertical semicircular canals in altering autonomic activity has been hypothesized, studies to-date attribute the evoked BP and HR responses to the otolith organs. The present study determined whether unilateral activation of the posterior (PC) or anterior (AC) semicircular canal is sufficient to elicit changes in BP and/or HR. The study employed frequency-modulated pulsed infrared radiation (IR:1863nm) directed via optical fibers to PC or AC of adult male Long-Evans rats. BP and HR changes were detected using a small-animal single pressure telemetry device implanted in the femoral artery. Eye movements evoked during IR of the vestibular endorgans were used to confirm the stimulation site. We found that sinusoidal IR delivered to either PC or AC elicited a rapid decrease in BP and HR followed by a stimulation frequency-matched modulation. The magnitude of the initial decrements in HR and BP did not correlate with the energy of the suprathreshold stimulus. This response pattern was consistent across multiple trials within an experimental session, replicable, and in most animals showed no evidence of habituation or an additive effect. Frequency modulated electrical current delivered to the PC and IR stimulation of the AC, caused decrements in HR and BP that resembled those evoked by IR of the PC. Frequency domain heart rate variability assessment revealed that, in most subjects, IR stimulation increased the low frequency (LF) component and decreased the high frequency (HF) component, resulting in an increase in the LF/HF ratio. This ratio estimates the relative contributions of sympathetic nervous system (SNS) and parasympathetic nervous system (PNS) activities. An injection of atropine, a muscarinic cholinergic receptor antagonist, diminished the IR evoked changes in HR, while the non-selective beta blocker propranolol eliminated changes in both HR and BP. This study provides direct evidence that activation of a single vertical semicircular canal is sufficient to activate and modulate central pathways that control HR and BP.